Community Participation in the Development of Village Teluk Rubiah Tourism Destinations, Muntok District - Septya Rini (Social Science Studies, 2023)
This article aims to find out the forms of organizational participation of the Teluk Rubiah Youth and Community Communication Forum (FKPMTR) in the development of a tourist village in Teluk Rubiah, Muntok District and to find out the factors that encourage and hinder it.This study uses a type of qualitative research. The results of this study indicate that participation in the TeluRubiah Iklim Village has gone very well. To maintain the existence of FKPMTR there are motivations that belong to them. One of his motivations was to obtain material at FKPMTR. This can happen because they get CSR funds from the government and companies to carry out their activities. The driving factor for tourism in the TelukRubiah IklimVillage is the enthusiasm and desire of FKPMTR members to participate in planning the development of a tourist village. There are also economic factors that influence them to participate due to their economic situation which can be considered less. Besides that, it turns out that there are still factors inhibiting FKPMTR in participating, such as the low awareness of some FKPMTR members for tourism development in TelukRubiah. Artikel ini bertujuan untuk mengetahui bentuk partisipasi organisasi Forum Komunikasi Pemuda dan Masyarakat Teluk Rubiah (FKPMTR) dalam pengembangan desa wisata di Teluk Rubiah Kabupaten Muntok serta mengetahui faktor-faktor yang mendorong dan menghambatnya. Penelitian ini menggunakan jenis penelitian kualitatif. Hasil penelitian ini menunjukkan bahwa partisipasi di Kampung Iklim Teluk Rubiah sudah berjalan dengan sangat baik. Untuk mempertahankan eksistensi FKPMTR ada motivasi yang dimiliki oleh mereka. Salah satu motivasinya adalah untuk mendapatkan materi di FKPMTR. Hal ini bisa terjadi karena mereka mendapatkan dana CSR dari pemerintah dan perusahaan untuk menjalankan aktivitasnya. Faktor pendorong pariwisata di Kampung Iklim Teluk Rubiah adalah semangat dan keinginan anggota FKPMTR untuk ikut serta merencanakan pengembangan desa wisata. Ada juga faktor ekonomi yang mempengaruhi mereka untuk berpartisipasi dikarenakan keadaan ekonomi mereka yang bisa dibilang kurang. Selain itu, ternyata masih ada faktor yang menghambat partisipasi FKPMTR, seperti rendahnya kesadaran sebagian anggota FKPMTR terhadap pengembangan wisata di Teluk Rubiah.